Community perspectives and participation in rangeland restoration: challenges and opportunities in the Eastern Cape, South Africa - Slayi, Mhlangabezi (Frontiers in Animal Science, 2025)
Rangeland degradation continues to pose significant ecological and economic challenges for rural communities in the Eastern Cape, South Africa, adversely affecting livestock productivity and ecosystem services. This study investigates community perceptions, awareness, and willingness to engage in rangeland restoration efforts. A mixed−methods approach was used, combining a structured survey of 150 respondents and focus group discussions (FGDs). Quantitative data were analyzed using chi−square and logistic regression analyses, while qualitative data were thematically coded to explore local narratives and deepen understanding. The results reveal that 73% of respondents recognize rangeland degradation as a serious issue, with 85% acknowledging its adverse impacts on livestock productivity. Willingness to participate in restoration was influenced by education (p = 0.031), access to resources (p = 0.011), and technical knowledge (p = 0.012), highlighting the role of education, land tenure security, and institutional support. Focus groups added nuance, indicating varied perceptions of “degradation” and “restoration” across participants, and revealed constraints related to resource access, financial limitations, and the nature of restoration activities envisaged. These findings underscore the importance of aligning restoration interventions with local perceptions, clarifying the scope of restoration practices, and embedding them within inclusive institutional and governance arrangements. Sustainable restoration in communal rangelands will require context−specific strategies that balance ecological priorities with rural livelihood needs.